Intranasal Fentanyl - An Effective First Line Analgesia for Children - Britnell, S (Emergency Nurse New Zealand, 2009)
Rapid and effective analgesia is important particularly when intravenous (IV) access is unavailable. Children present unique challenges and achieving effective analgesia and this may often be delayed due to staff skill and availability, patient and caregiver anxiety combined with varying responses to pain and difficult IV access. Fentanyl is a rapid acting medication which takes 2 minutes to reach serum therapeutic levels. This makes it a viable choice of analgesia while longer term pain relief options are considered. The decision to utilise the IV route and administration of Fentanyl is nurse initiated on triage in CED in collaboration with medical staff who prescribe the medication, this is commenced at triage to decrease the time to analgesia.